Structural dynamics and binding free energy of neral-cyclodextrins inclusion complexes: molecular dynamics simulation. Issue 13 (2nd November 2017) - Wongpituk, Peerapong; Nutho, Bodee; Panman, Wanwisa; Kungwan, Nawee; Wolschann, Peter; Rungrotmongkol, Thanyada; Nunthaboot, Nadtanet
Abstract: The inclusion complexation of neral, a cis -isomer of citral found in lemon grass ( Cymbopogon citratus Stapf), and four different types of cyclodextrin (β-cyclodextrin (βCD), 2, 6-dimethyl-βCD (2, 6DMβCD), 2, 6-dihydroxypropyl-βCD (2, 6DHPβCD), and 2-hydroxypropyl-βCD (2HPβCD)) was investigated using molecular docking and molecular dynamics simulation approaches. The simulations show that the neral/CD inclusion complex could be formed in an aqueous solution with a 1:1 ratio. Three possible binding orientations were assessed for the encapsulation of neral ( 1 neral, 7 neral, and u neral) inside the hydrophobic interior of the host molecule. The u neral, in which both aldehyde and alkyl terminals point outward on the secondary rim of the CD, was observed to be the most preferential conformation in all neral/CD complexes. The theoretical calculations of the binding ability of the host–guest inclusion complexes agreed well with the experimental data, thereby supporting that the neral could bind inside the hydrophobic cavity of all CDs with nearly the same potency.